Empowering School Staff to Implement Effective School Mental Health Services. (May 2022) - Kern, Lee; Weist, Mark D.; Mathur, Sarup R.; Barber, Brian R.
In this article, we follow up on recommendations from the Division for Emotional and Behavioral Health (DEBH) for providing school mental health (SMH) services by offering additional implementation suggestions for teachers and school staff. We highlight the need for and urgency of SMH services, particularly during and after the pandemic, and also consider broad issues that interfere with the success of SMH. We then provide a number of specific recommendations for integrating the delivery of SMH services within a tiered system of supports that are intended to empower school staff to move toward implementation. Last, we address how effective implementation can be facilitated by strong administrative support along with capacity building.